Diffusion of calcium ions in one-third of root canals after administration of high molecular Chitosan nanohydroxyapatite medicament (In Vitro) - Widya Nurul AKMALIA; Trimurni ABIDIN (Dentistry Faculty, 2021)
ABSTRACT Calcium hydroxide is currently the gold standard medicament. Still, it has the disadvantage of leavinga residue on the surface of the root canal wall. Hence, it can interfere with the setting time and adhesion of the sealermaterial to the root canal wall. This study aims to determine the ability of calcium ion diffusion in one-third of theroot canal after administration of nanohydroxyapatite medicament with a different vehicle than calcium hydroxide.This study used 24 mandibular premolars extracted, decorated, and prepared, then grouped into four treatmentgroups. Based on the paired T-test, the study results showed no significant effect of calcium ion diffusion in group B(p = 0.739) on the 7th and 14th days. The ANOVA test results showed no significant difference in calcium ion diffusion between groups A, B, and C. on the 7th day of testing (p=0.773) and the 14th day (p=0.661). In conclusion, there was no effect and difference in the diffusion of calcium ions in the apical third after administration ofmedicament nanohydroxyapatite vehicle bidisstilled water and nanohydroxyapatite vehicle nanochitosan compared tocalcium hydroxide on the 7th and 14th day KEYWORDS: diffusion, calcium hydroxide, ion calcium, nanohydroxyapatite, nano chitosan, vehicle